2015
DOI: 10.1088/2041-8205/806/1/l14
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Simulations of Black Hole–neutron Star Coalescence: The Jet Emerges

Abstract: We perform magnetohydrodynamic simulations in full general relativity (GRMHD) of a binary black hole-neutron star on a quasicircular orbit that undergoes merger. The binary mass ratio is 3 : 1, the black hole initial spin parameter a/m = 0.75 (m is the black hole Christodoulou mass) aligned with the orbital angular momentum, and the neutron star is an irrotational Γ = 2 polytrope. About two orbits prior to merger (at time t = t B ), we seed the neutron star with a dynamically weak interior dipole magnetic fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
289
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(309 citation statements)
references
References 44 publications
19
289
0
1
Order By: Relevance
“…During the short ( 1 s) accretion phase a relativistic jet can be launched via different mechanisms (involving neutrino annihilation and/or magnetic fields), finally producing the SGRB. This picture is supported by recent numerical simulations ( [9,10] and references therein), which have shown that a massive (∼ 0.1 M ) accretion torus is naturally formed when the merger leads to the prompt formation of a spinning BH.…”
Section: Introductionsupporting
confidence: 56%
“…During the short ( 1 s) accretion phase a relativistic jet can be launched via different mechanisms (involving neutrino annihilation and/or magnetic fields), finally producing the SGRB. This picture is supported by recent numerical simulations ( [9,10] and references therein), which have shown that a massive (∼ 0.1 M ) accretion torus is naturally formed when the merger leads to the prompt formation of a spinning BH.…”
Section: Introductionsupporting
confidence: 56%
“…The GRB is understood as consequence of highly collimated, ultrarelativistic polar outflows or jets of low-density plasma or Poynting flux, whose energy is partly converted to γ-rays at distances of 10 12 -10 13 cm, far away from the compact remnant (e.g., Piran 2004). The annihilation of neutrinoantineutrino pairs radiated by the hot accretion torus as possible energy sources to drive these jets, is discussed (e.g., Eichler et al 1989;Jaroszynski 1993;Woosley 1993;Popham et al 1999;Ruffert & Janka 1999;Di Matteo et al 2002;Birkl et al 2007;Dessart et al 2009;Zalamea & Beloborodov 2011), also considering the energy release by magnetohydrodynamic effects, Poynting flux (e.g., Blandford & Znajek 1977;McKinney & Blandford 2009;Paschalidis et al 2015), and electron-positron pair production (Usov 1992) associated with ultra-strong magnetic fields threading the BHtorus system or MNS and their environments, as possible energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the emergence of a jet-favorable magnetic field configuration in NS-NS/BH mergers (Dionysopoulou et al 2015;Kiuchi et al 2015;Paschalidis et al 2015), the efficiency of neutrino production in accretion disks and tori with steadystate accretion rates (e.g., Popham et al 1999;Di Matteo et al 2002;Chen & Beloborodov 2007), the efficiency of neutrino-antineutrino (nn-) annihilation above the poles of a BH (e.g., Birkl et al 2007;Zalamea & Beloborodov 2011;Richers et al 2015), or the jet acceleration and collimation by the interaction with the accretion torus, non-relativistic winds (Aloy et al 2005;Murguia-Berthier et al 2014), and the ejecta from dynamical NS-NS mergers (Nagakura et al 2014;Duffell et al 2015), have all been studied. Also, time-dependent and self-consistent hydrodynamic simulations of BH-torus remnants including some neutrino treatment have been performed to study neutrino emission and annihilation (Ruffert & Janka 1999;Setiawan et al 2004Setiawan et al , 2006Fernández & Metzger 2013;Foucart et al 2015;Just et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…By combining GW and EM signals from NSNSs one can in principle test relativistic gravity and constrain the behavior of matter at super-nuclear densities. Furthermore, NSNS mergers may offer explanations to long-standing astrophysical puzzles, such as the nature of short-hard gamma ray burst progenitors [14][15][16], and the origin of r-process elements [17]. …”
mentioning
confidence: 99%